Procesos cognitivos y su influencia en el estado emocional de un joven de 23 años privado de su libertad en el CRS Babahoyo - Gaibor Baldeon, Maria Fernanda (2021)
The present psychological intervention aims to identify through Rational Emotive Therapy techniques if cognitive processes influence the emotional state of a 23-year-old young man deprived of his liberty in the CRS of Babahoyo canton. It should be mentioned that the methodology used in this work is qualitative and is aimed at the scientific investigation of variables such as: Cognitive processes and emotional state, which are exposed in the present case study, on the other hand it was considered to establish in This work techniques of the TREC, which allowed the objective to be fulfilled in its entirety thanks to the therapeutic plan that is proposed in the psychological intervention, which is aimed at offering the patient an Individual Therapy to modify their beliefs and therefore their behavior and emotional state all this in order to provide the patient with a favorable prognosis.